2018
DOI: 10.1038/s41598-018-28920-x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary dynamics of mycorrhizal symbiosis in land plant diversification

Abstract: Mycorrhizal symbiosis between soil fungi and land plants is one of the most widespread and ecologically important mutualisms on earth. It has long been hypothesized that the Glomeromycotina, the mycorrhizal symbionts of the majority of plants, facilitated colonization of land by plants in the Ordovician. This view was recently challenged by the discovery of mycorrhiza-like associations with Mucoromycotina in several early diverging lineages of land plants. Utilizing a large, species-level database of plants’ m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 51 publications
(78 reference statements)
1
47
0
4
Order By: Relevance
“…At present, molecular and paleo-biological studies have shown how the origin of AMF and of terrestrial plants occurred simultaneously over time (about 470 million years ago) from epiphytic fungi that grew on the surface of the first vascular plants. They were also necessary for the success of plant terrestrial colonization (Feijen et al, 2018;Rimington et al, 2018;Strullu-Derrien et al, 2018). Thus, ECMF emerged evolutionarily after AMF, once the plants had already colonized the earth (Hoeksema et al, 2018).…”
Section: Mycorrhizal Fungimentioning
confidence: 99%
“…At present, molecular and paleo-biological studies have shown how the origin of AMF and of terrestrial plants occurred simultaneously over time (about 470 million years ago) from epiphytic fungi that grew on the surface of the first vascular plants. They were also necessary for the success of plant terrestrial colonization (Feijen et al, 2018;Rimington et al, 2018;Strullu-Derrien et al, 2018). Thus, ECMF emerged evolutionarily after AMF, once the plants had already colonized the earth (Hoeksema et al, 2018).…”
Section: Mycorrhizal Fungimentioning
confidence: 99%
“…Ancestral reconstruction supports Mucoromycotina symbiosis evolving before Glomeromycotina symbiosis in liverworts. Given current uncertainties surrounding the order of divergence of the three bryophyte lineages (liverworts, hornworts, and mosses) and the monophyly of bryophytes (Puttick et al 2018; de Sousa et al 2019), it is not yet possible to confirm or otherwise refute the recent, novel hypothesis, based on multidisciplinary evidence, of Mucoromycotina having formed the ancestral plant-fungus symbiosis (Bidartondo et al 2011; Field et al 2015a; Feijen et al 2018).…”
Section: The Origins Of Fungal Symbiosis In Liverwortsmentioning
confidence: 99%
“…Mycorrhizal symbiosis, an association between soil fungi and plant roots, has been hypothesized to be one of the critical evolutionary innovations essential for the successful colonization of land by early land plants, subsequently leading to their radiation and providing the foundation for the majority of the extant terrestrial ecosystems (Delaux, 2017;Feijen, Vos, Nuytinck, & Merckx, 2018;Field, Pressel, Duckett, Rimington, & Bidartondo, 2015;Martin, Uroz, & Barker, 2017). Based on the morphology of the interaction and the identity of the partners, four major types of mycorrhiza have been recognized (arbuscular mycorrhiza, ectomycorrhiza, ericoid mycorrhiza and orchid mycorrhiza), and together they include over 90% of extant land plant species and up to 10% of fungal species (Brundrett & Tedersoo, 2018;van der Heijden, Martin, Selosse, & Sanders, 2015).…”
Section: Introductionmentioning
confidence: 99%